2017
DOI: 10.1590/0102-311x00094016
|View full text |Cite
|
Sign up to set email alerts
|

Depressão entre puérperas: prevalência e fatores associados

Abstract: Cad. Saúde Pública 2017; 33 (9) Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
39
1
85

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 21 publications
9
39
1
85
Order By: Relevance
“…These education standards are in agreement with other analyzed studies and corroborate the idea that low educational level may contribute to the development of PPD. [22][23][24] Some studies still provide a view between age and PPD: younger mothers presented depressive symptoms more frequently. The present study did not verify statistical relevance related to the age of the mother, since out of the 30 patients with probable PPD, the majority (14) were between 20 and 24 years of age, 11 were between 25 and 40 years old and only 5 patients were between the ages of 15 and 19, considered at greater risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These education standards are in agreement with other analyzed studies and corroborate the idea that low educational level may contribute to the development of PPD. [22][23][24] Some studies still provide a view between age and PPD: younger mothers presented depressive symptoms more frequently. The present study did not verify statistical relevance related to the age of the mother, since out of the 30 patients with probable PPD, the majority (14) were between 20 and 24 years of age, 11 were between 25 and 40 years old and only 5 patients were between the ages of 15 and 19, considered at greater risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the factors highlighted above, several studies have revealed that previous history of psychiatric illness or previous psychological problem of the mother, including the melancholy of motherhood, also predicted the subsequent occurrence of PPD. 24,25,[37][38][39] The high prevalence of PPD nowadays reinforces its significance as a public health problem, requiring prevention and treatment strategies. [40][41][42] A careful follow-up of mothers, especially those with low incomes, through integrated actions that take into account the variables associated with depression, can prevent serious personal and family problems that result from PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum depressive symptoms were significantly associated with depression at some point in pregnancy or sadness during the last trimester of pregnancy, which corroborates the findings of this research and supports systematic screening for depression in antenatal care and in maternity wards. (18,19) The violence suffered during pregnancy figured as a negative determinant for depressive symptoms in the immediate postpartum, enhancing the recognition already present in the literature of the severe consequences of gestational violence for the woman and the baby. A Japanese research has pointed out that both physical violence and verbal violence are causal determinants for the development of depressive symptoms in mothers during pregnancy, emphasizing the importance of nurses to identify violence during their care of pregnant women and to refer timely for psychosocial support, as a way to prevent depressive symptoms before and after childbirth (19) and also to reduce its negative repercussions on the mother-child binomial.…”
Section: Discussionmentioning
confidence: 83%
“…(29) In the city of Rio Grande/RS, using the same scale and cutoff point, the prevalence was 14%, and the measure was taken on the second day postpartum. (18) In view of the above, the comparison of the prevalence rate obtained in Botucatu with others found in Brazil and abroad should be performed with caution, considering the differences related to the evaluation moment, the scale used and the cutoff point adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Quando ocorre durante a gravidez, a depressão acarreta consequências alarmantes com repercussões negativas não apenas na saúde materna, mas também fetal (2)(3)(4)(5)(6)(7)(8) , o que enfatiza a necessidade e a relevância da triagem desse transtorno na gravidez (9) , assim como a identificação precoce das mulheres gestantes em risco de desenvolvê-lo (10) .…”
unclassified